Length–weight relationships of 20 fish species from Pahang River, Maran district, Pahang, Malaysia - Abd. Rashid, Zulkafli; Azmai, Mohammad Noor Amal; Shohaimi, Shamarina; A., Mustafa; A. H., Ghani; S., Hashim; M. I., Anuar; P., Hasfairi (Blackwell Verlag GmbH, 2015)
This study reports the length–weight relationships (LWR) of 20 fish species from the Pahang River, Maran district, Pahang, Malaysia. The river supplies fishes mainly for local consumption and is a principal body of water for freshwater aquaculture in Malaysia. A total of 12 LWR of fishes were unknown to FishBase, and five new maximum lengths of fishes were identified from the study.